CHANGING ROLE OF FATHERS WITH IN THE FAMILY UNIT - Rubina Kumari (International Journal of Multidisciplinary Research and Studies, 2021)
The function that men play as dads is one that is always shifting and developing as time goes on. Traditionally, the act of fathering has been regarded as something that is historically specific, culturally singular, and the product of social construction. Fathering behaviours are always being redefined and negotiated as men attempt to strike a balance between the external pressures of their jobs and the internal constructions they have of the kind of dads they wish to be (Olmstead, Futris, & Pasley, 2009). The notion of what it means to be a man and a father in a culture may and will change throughout time, and with it, the construction of masculinity and the manner in which men approach the responsibility of parenting (Pleck & Pleck, 1997). Deconstruction of the traditional function of men in families is occurring concurrently with the emergence of a new male identity that has resulted in a rethinking of the traditional position of men in their families (Day & Lamb, 2004). Given that the determinants of fathering behaviors are culturally influenced and socially constructed, and that they change over time, it is important to recognize that the manner in which a man enacts the role of fatherhood is greatly influenced by a multitude of factors, many of which derive from the internal motivations and experiences that he has had throughout his life. The act of fathering also becomes more complicated over the course of a person's lifetime due to the fact that both the father and his kid are constantly required to reconcile internal wants, desires, and conflicts with external pressures and expectations. The missing piece in the puzzle of how men create their fathering role has been the realisation of the intricacies of the connections that men have with their own dads. The manner in which one was fathered shapes their own paternal approach. The discussion of the significance of extending the role of the father beyond that of an idealizing self-object into the position of a supplier of mirroring and twinship self-object functions will be the primary emphasis of this essay.